Condrosulf®: Structural Characterization, Pharmacological Activities and Mechanism of Action - Volpi, Nicola (Current Medicinal Chemistry, 2014)
Condrosulf® is a pharmaceutical formulation containing chondroitin sulfate (CS) as an active component possessing high quality and purity and standardized properties. CS is currently applied as a SYSADOA (Symptomatic Slow Acting Drug for Osteoarthritis) agent in Europe in the treatment of osteoarthritis (OA). Furthermore, Condrosulf® and pharmaceutical grade CS have also been proven to possess structure-modifying effects belonging to the S/DMOAD (structure/disease modifying anti-osteoarthritis drug) class. This review summarizes current knowledge on CS/Condrosulf® structure and its properties, its pharmacological activity as proved by many clinical trials and metaanalysis studies and focuses attention on its mechanisms of action in the pathophysiology of osteoarthritic joint tissues. Finally, future perspectives are discussed in connection with the possibility to apply new outcome measures, such as MRI and biomarkers, which can yield important advances in the use of Condrosulf® as well as the development of new drugs with different structures useful in particular for the treatment of inflammatory symptoms and able to retard the progression of arthritis.
Keywords: chondroitin sulfate